Hypobaric-ischemic conditions produce glutamate-like cytopathology in infant rat brain - Ikonomidou, C (J Neurosci, 1989)
We present a new animal model of perinatal hypoxic/ischemic brain damage and compare this type of brain damage with the excitotoxic type of damage previously described in the brains of infant rats and monkeys treated systemically with glutamate (Glu). Ten-d-old rats with unilateral occlusion of the common carotid artery were subjected to hypobaric conditions for 75 min and sacrificed 0–4 hr later for light and electron microscopic brain examination. The mortality rate was relatively low (12%), and brain damage was evident ipsilateral to the ligated carotid in 94% of surviving animals 4 hr after termination of the hypobaric event. Regions most frequently affected were the medial habenulum, dentate gyrus, caudate nucleus, frontoparietal neocortices, olfactory tubercle, and several thalamic nuclei. The acute cytopathological changes, primarily edematous degeneration of neuronal dendrites and cell bodies, evolved very rapidly, with some neurons manifesting end-stage necrosis at 0 hr (immediately after hypobaric exposure) and others developing such changes over a 1–4-hr period. We conclude that the neurodegenerative reaction induced in infant rat brain by hypoxia/ischemia is indistinguishable from the excitotoxic type of damage exogenous Glu is known to cause. Moreover, in a companion study (Olney et al., 1989) we show that MK-801, a powerful antagonist of the N-methyl-D-aspartate receptor complex (subtype of Glu receptor), protects against neuronal degeneration in this hypobaric/ischemic model. Our results reinforce other recent evidence suggesting that hypoxic/ischemic brain damage is mediated by endogenous Glu or related excitotoxins.